Evidence for mu opioid receptor on mouse spleen lymphocytes. - Wu Tong; Li Xiao-yu (Acta Pharmacologica Sinica, 2016)
AIM: Using ohmefentanyl (Ohm), a high affinity mu opioid receptor agonist, to find whether mu opioid receptor exists on mouse spleen lymphocytes. METHODS: The proliferation rates of T-lymphocytes and B-lymphocytes were determined under various concentrations of Ohm with or without naloxone(Nal) in vitro. Binding characteristics of [3H] Ohm with mice spleen lymphocytes were studied by radioligand assays. RESULTS: Ohm 0.1 pmol.L(-1)-1 nmol.L-1 enhanced Con A-induced spleen T-cell proliferation in vitro. Nal 50 mumol.L-1, which per se enhanced the T-cell proliferation, blocked the enhancing effects of Ohm. However, Ohm had no effect on B-cell proliferation. Furthermore, a satisfactory saturable, specific, and reversible binding was demonstrated with Kd of (6.9 +/- 0.6) nmol.L-1, Bmax of (74 +/- 6) fmol/10(7) cells. The binding of [3H] Ohm was blocked by unlabeled Ohm or Nal. CONCLUSION: Stimulating effects of Ohm on lymphocytes were mediated by opioid receptors. Mouse spleen lymphocytes present mu opioid receptors.